Language Games: Concept, Types and Its Role For Enhancing The Linguistic Ability Of Young Learners - Houssam Eddine Taouririt; Imane Chacha (Ijaz Arabi Journal of Arabic Learning, 2023)
Language games are innovative learning for teaching the Arabic language to young learners. This is mainly due to the satisfactory results they provide on the level of language achievement and the development of mental abilities, in addition to the positive impact on the child's psyche.  This research addresses the importance of this kind of educational aid. It highlights its positive effects on the educational process in general, the development of the emerging child's language abilities, and the response of young learners to these means. Provide an accurate and precise description of the nature of language games, the most important types, and the criteria for their use. And the positives of employing them in the teaching and learning process using the descriptive method, an attempt to extract data that helps us build a clear perception that qualifies us to derive valuable results. Through this research, we have concluded that language games contribute directly to improving the level of the learner and improving the conditions of the educational process to ensure the development of the learner's language level and enhance his skills by breaking the monotony and routine. Associated with the traditional learning process and encouraging the learner to engage in the learning process, interact with it, and integrate with it.